Revisiting Official History in Evangel Athial’s Hitler and the Decline of Shah Dynasty - Singh, Raj Kishor (Molung Educational Frontier, 2020)
This article aims to analyze Athial’s Hitler and the Decline of Shah Dynasty to prove that the author reimagines and rewrites official history in his novel with combination and blurring of fact and fiction. It is studied from theoretical parameters of historiographic metafiction. Through an amalgamation of fact and fiction, the novel challenges the traditional version of the official history of Nepal and Germany. The subjectivity inherent in historiographic narratives is further explored through Athial’s representation of historical character Hitler in the novel. The presence of major characters creates confusion about the nature of the novel as a work of fiction or as historiographic account. Through the use of irony and supernatural elements, Hitler and the Decline of Shah Dynasty becomes a parody of historiographic narratives which claim to be objective. The blurring of the boundaries between fiction and history and constructedness of history through discourse is the main idea in this paper. The writer imitates the genre of the historical novel but reveals its limitations and corresponds to what Linda Hutcheon calls historiographic metafiction. The novel mines the elements of the then history of Hitler, Germany, and Nepalese Shah Dynasty with the personal history of the author to revise and redefine the official version of history. This revisiting of mainstream history helps to establish the notion of plurality of historical accounts and a rejection of objectivity in historical writings. This novel has metafictional mode of writing, and the author represents metafictional parody in which historical incidents are repeated with a difference to show that history is discourse and is always open to interpretation.